Engineering of a polydisperse small heat-shock protein reveals conserved motifs of oligomer plasticity - Mishra, S; Chandler, S; Williams, D; Claxton, D; Koteiche, H; Stewart, P; Benesch, J; Mchaourab, H (Elsevier, 2018)
Small heat-shock proteins (sHSPs) are molecular chaperones that bind partially and globally unfolded states of their client proteins. Previously, we discovered that the archaeal Hsp16.5, which forms ordered and symmetric 24-subunit oligomers, can be engineered to transition to an ordered and symmetric 48-subunit oligomer by insertion of a peptide from human HspB1 (Hsp27). Here, we uncovered the existence of an array of oligomeric states (30–38 subunits) that can be populated as a consequence of altering the sequence and length of the inserted peptide. Polydisperse Hsp16.5 oligomers displayed higher affinity to a model client protein consistent with a general mechanism for recognition and binding that involves increased access of the hydrophobic N-terminal region. Our findings, which integrate structural and functional analyses from evolutionarily distant sHSPs, support a model wherein the modular architecture of these proteins encodes motifs of oligomer polydispersity, dissociation, and expansion to achieve functional diversity and regulation. Through manipulation of the sequence of an inserted peptide, Mishra et al. generated variants of the monodisperse archaeal Hsp16.5 that assemble into oligomers of different sizes and structures. Measurements of the affinity of these variants toward a client protein reinforces the relationship between oligomer size, polydispersity and chaperone efficiency.